Arts-based methodologies to explore Asian-Canadian youth identities in the Greater Toronto Area: Sharing some implementation experiences from the field - Madzima, Sheena; Karunakaran, Amirtha; Vazquez, Luz Maria; Khanlou, Nazilla (INYI Journal, 2020)
Cultural identity is a complex, fluid and context bound concept. Cultural identity is informed by immigrant and second-generation youths’ experiences of adaptation and integration. Cultural identity has also been linked to youth mental health and wellbeing. Research recognizes the need to develop research tools to better capture and understand youths’ lived experiences with their identity and integration in multicultural settings. We present preliminary research findings from our community-based project that applied arts-based methodologies to explore Asian-Canadian youth identities in the Greater Toronto Area in Canada. Inclusion criteria were (i) youth between the ages of 16-29 and (ii) who self-identify as Asian or Asian-Canadian. We organized two workshops with youth participants. In workshop 1 we applied visual arts: Self-Portrait and a Relational Map. In workshop 2 we applied drama (Readers’ Theatre). Youth feedback highlighted the effectiveness of arts-based methodologies in (i) helping youth to discuss their lived experiences without feeling like they were under evaluation, (ii) providing a universal way of communicating their experiences and, (iii) allowing youth to think of issues that participants had not previously reflected on. We also shared some implementation experiences. This pilot study informed implementation strategies for a current larger project that has the objective of evaluating the effectiveness of arts-based methodologies to explore Asian-Canadian youth identities.